Imaging and quantifying the different crystalline structures of polypropylene with the atomic force microscope - Klash, Abdalah (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.